Interconnection and damping assignment control based on modified actor–critic algorithm with wavelet function approximation - Gheibi, Amir; Ghiasi, Amir Rikhtehgar; Ghaemi, Sehraneh; Badamchizadeh, Mohammad Ali (ISA transactions, 2020)
Passivity-based control (PBC) is model-based, and as a result, it is affected by uncertainties. Besides, for some PBC designs, partial differential equations (PDEs) should be solved in order to obtain the parameters of the controller. Actor–critic (AC) algorithm has been used to regulate PBC parameters instantaneously and solve PDEs online. Despite the benefits of this algorithm, it cannot handle disturbance. The main purpose of this paper is to modify the AC algorithm with an online wavelet function approximation to improve its performance. The proposed method uses PBC and the modified AC algorithm to attenuate the effects of uncertainties. Moreover, the stability analysis is investigated for a nonlinear system. The results show that the new method can handle disturbance and uncertainties more proper than other methods. •A realistic model of the boost converter with time-varying load and disturbance is considered.•A new nonlinear control strategy is used for designing the controller.•The new method utilizes passivity based control (PBC) and the modified actor–critic (AC) algorithm.•Online wavelet function approximation (OWFA) is applied as an approximator.